Pengaruh Kebijakan Harga, Kualitas Produk dan Tempat Terhadap Keputusan Pembelian Sayuran Hidroponik di Kelompok Wanita Tani (KWT) Tamara 09 Kelurahan Ciketingudik Kecamatan Bantargebang Kota Bekasi - Ika Septarina Sari; Sugiyanto; Imas Wildan Rafiqah (Fakultas Pertanian Universitas Borobudur, 2024)
This research aims to determine the influence of price policy variables, product quality and location on consumer decisions in purchasing hydroponic vegetables at KWT Tamara 09, Ciketingudik Village, Bantargebang District, Bekasi City. The data analysis method used in this research is quantitative with a total of 75 respondents. The variables used in this research are independent variables consisting of price policy, product quality and place, while the dependent variable is purchasing decisions. The results of the research show that: 1. The independent variables, namely price policy, product quality and place, have a simultaneous influence on consumer decisions in purchasing hydroponics at KWT Tamara 09, 2. The price policy variable has a significant and positive partial influence on consumer decisions in purchasing hydroponic vegetables at KWT Tamara 09, 3. The product quality variable has a significant and positive partial influence on consumer decisions in purchasing hydroponic vegetables at KWT Tamara 09, 4. The place variable has a significant and positive partial influence on consumer decisions in purchasing hydroponic vegetables at KWT Tamara 09